Estudo epidemiológico, espacial e temporal, na análise da associação entre poluição do ar e o número de atendimentos hospitalares por causas respiratórias em crianças, na Região da Grande Vitória, ES - Matos, Emerson Pedreira (2012)
This research aims to investigate the association between short-term air pollution, the pollutants through PM10, SO2, NO2, O3 and CO, and respiratory e ects in children under 6 years through spatial and temporal distribution in the Greater Vitória, Brazil. To verify this relationship, we used the generalized additive model Poisson regression, with the dependent variable the daily number of visits for respiratory illnesses and independent variables, daily concentrations of air pollutants, temperature, humidity , among others. The methodology consisted of comparing the analyzes in situ, ie, broken in places with the estimate for the entire region. The results showed that some e ects were seen only in localities disaggregated by region. This is an expected result, since the use of the average of all stations tends to smooth out the data and thus reduce the variability, which hides some e ects in modeling.